Labview based driver for charge-coupled device linear image sensor - Ramli, N. (Penerbit UTM Press, 2011)
This paper describes the development of LabVIEW based driver for charge-coupled device (CCD) linear image sensor in optical tomography system. The Sony ILX551A CCD linear image sensor contains 2048 effective pixels, each pixel approximately 14 microns in size. The sensor requires suitable clocking signals (FROG and FCLK) before the pixel values that represent the attenuated optical intensity can be serially read. The output from the CCD is the optical intensity measured in voltage or shadow of the object intercepting the optical beam, pathlength between light source and the CCD linear image sensor. When solid particles blocking certain area of the optical path length, the shadow of the object will be casted on several affected pixels of the linear image sensor, and value on the output signal will be obtained. The exact location of objects on output signal produced for various conditions is important in order to verify the proper clocking signals generated for Sony ILX551A. The results demonstrate that the clocking signal at 1MHz frequency for the CCD Sony ILX551A is successfully generated and capable of acquiring tomographic data.